Cyrilovite from Cyrilov, western Moravia, Czech Republic; new data on the type material - Novak,M.; Sejkora,J.; Cooper,M.A. (Journal of the Czech Geological Society, 2000)
The type material of cyrilovite from Cyrilov was studied by the means of electron microprobe, X-ray powder diffraction and IR spectroscopy. Cyrilovite is close to the end-member composition NaFe3+3 (OH)4 (PO4)2. 2 H2O with minor concentrations of Al (0.00-0.10 apfu) and Ca (0.01-0.05 apfu), insignificant substitutions Fe3+ → Al and CaFe2+ → NaFe3+ are indicated. The lattice parameters - a = 7.3227(3), c = 19.332(1) Å, V = 1036.61(8) Å3 and density Dcalc = 3.112 g.cm-3 of cyrilovite calculated from powder data are very close to those obtained from the single crystal refinement - a = 7.3255(4), c = 19.328(2) Å, V = 1037.2(2) Å3 and Dcalc = 3.106 g.cm-3, respectively, (Cooper et al. 2000) and to cyrilovite from other localities. The infrared absorption spectrum is very close to that of cyrilovite from Cyrilov published by Tarte et al. (1984). Two structurally nonequivalent water molecules and hydroxyls may be present in the crystal structure of cyrilovite. The number of (PO4) vibrations may also indicate that two structurally nonequivalent (PO4) groups are present in the crystal structure but not detected by the crystal structure analysis, possibly indicating lower symmetry.
Keywords: Cyrilovite; electron microprobe; X-ray powder study; IR spectroscopy; Cyrilov; Moravia